Sorption of Cr(III) from aqueous solutions by spent brewery grain - Ferraz, A. I. (2005)
Two types of spent brewery grains were tested for Cr(III) uptake from aqueous solutions: not treated spent grains (NTSG), obtained by abundant washing of spent grain obtained from a Portuguese brewing industry with distilled water, and treated spent grain (TSG), prepared by treating NTSG with NaOH 0.5 M for four hours followed by washing with distilled water. Both materials were mixed with chromium solutions (50 and 100 mg Cr(III)/L), varying medium pH from 3 to 5. Maximum metal uptake occurred at pH 5. Langmuir isotherm model well describes Cr(III) biosorption by NTSG and TSG. The maximum uptake capacity obtained was 17.84 mg Cr(III)/g NTSG and 13.87 mg Cr(III)/g TSG. Considering that Langmuir constant, b, reflecting the affinity between the sorbent and the sorbate is lower for NTSG (0.0749 L/mg) it is possible to conclude that the alkalis treatment does not improve spent grain uptake capacity for Cr(III).